BARD1 mediates TGF-β signaling in pulmonary fibrosis. Issue 1 (December 2015) - André, Pierre-Alain; Prêle, Cecilia; Vierkotten, Sarah; Carnesecchi, Stéphanie; Donati, Yves; Chambers, Rachel; Pache, Jean-Claude; Crestani, Bruno; Barazzone-Argiroffo, Constance; Königshoff, Melanie; Laurent, Geoffrey; Irminger-Finger, Irmgard
Abstract Background Idiopathic pulmonary fibrosis (IPF) is a rapid progressive fibro-proliferative disorder with poor prognosis similar to lung cancer. The pathogenesis of IPF is uncertain, but loss of epithelial cells and fibroblast proliferation are thought to be central processes. Previous reports have shown thatBARD1 expression is upregulated in response to hypoxia and associated with TGF-β signaling, both recognized factors driving lung fibrosis. Differentially spliced BARD1 isoforms, in particular BARD1β, are oncogenic drivers of proliferation in cancers of various origins. We therefore hypothesized that BARD1 and/or its isoforms might play a role in lung fibrosis. Methods We investigatedBARD1 expression as a function of TGF-β in cultured cells, in mice with experimentally induced lung fibrosis, and in lung biopsies from pulmonary fibrosis patients. Results FL BARD1 and BARD1β were upregulated in response to TGF-β in epithelial cells and fibroblastsin vitro andin vivo . Protein and mRNA expression studies showed very low expression in healthy lung tissues, but upregulated expression of full length (FL) BARD1 and BARD1β in fibrotic tissues. Conclusion Our data suggest that FL BARD1 and BARD1β might be mediators of pleiotropic effects of TGF-β. In particular BARD1β might be a driver of proliferation and of pulmonary fibrosis pathogenesis and progression and represent a target for treatment.